PERANAN LEGENDA PUTRI HIJAU DI DESA SEBERAYA KECAMATAN TIGA PANAH KABUPATEN KARO DALAM PENULISAN SEJARAH LOKAL - Sabrina Oktavilyana; Rahmawati; Lila Pelita Hati; Lestari Dara Cinta Utami (Bajang Institute, 2023)
This study examines the legend of Putri Hijau in Seberaya Village, Tiga Panah District, Karo Regency and its role in local history writing. This study aims to find out the version of the Seberaya Village version of the Putri Hijau legend and the relics found in Seberaya Village. This article contains a novelty in it because it has a different perspective on Putri Hijau compared to previous writings, using the point of view of the karo community in Seberaya Village. This study uses the historical method which has 4 stages, namely heuristics, criticism, interpretation, and historiography. The type of research used is qualitative research by making in-depth observations. The formulation of the problems in this study are: (1) what is the connection between the legend of Putri Hijau and the local history of Seberaya Village?, (2) what are the legacies of the legend of Putri Hijau found in Seberaya Village?. It can be seen from the results of this research that Putri Hijau was born and grew up in Seberaya Village, she grew into a very beautiful girl. It is believed that Putri Hijau is still in Seberaya Village and will continue to protect the village from evil disturbances and disasters. There are also relics in this village, one of which is the Lauprik cave